Spurious tricuspid regurgitation: Three conditions mimicking tricuspid regurgitation diagnosed at operation - Brown, A. Hedley (1973)
Brown, A. H., and Braimbridge, M. V. (1973).Thorax, 28, 495-497. Spurious tricuspid regurgitation: Three conditions mimicking tricuspid regurgitation diagnosed at operation. The diagnosis of tricuspid incompetence is difficult. Three patients are described in whom the diagnosis of tricuspid regurgitation was made but disproved by the findings at surgery. The first patient had aortic regurgitation, mitral regurgitation from chordal rupture, and constrictive pericarditis; the right atrium was compressed between the pulsating left atrium and the tight pericardium. The chordal rupture caused the mitral murmur to radiate parasternally. The second patient had severe mitral and aortic regurgitation and an interatrial septal defect with transmission of the left-sided `v' waves to the right atrium. The third patient had an iatrogenic Gerbode defect from a previously repaired ostium primum atrial septal defect. Intracardiac phonocardiography failed to distinguish the anatomical situation from tricuspid regurgitation. The best assessment of tricuspid valvular disease is still that of the surgeon at operation.